Pengembangan Media Animasi Perubahan Energi untuk Meningkatkan Pemahaman Konsep IPA Pada Siswa Kelas IV Sekolah Dasar - Lilis Anggraini; Nirwana Anas (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Conceptual understanding refers to students’ ability to identify, explain, describe, distinguish, classify, and draw conclusions using their own words. This study aims to examine the process of developing animated media, assess its suitability as a learning medium, and determine students’ responses in improving their conceptual understanding of science material on energy transformation among fourth-grade elementary school students. This study uses a Research and Development (R&D) method based on the ADDIE model, involving 29 students. Data were collected through interviews, concept comprehension tests, validation sheets for media and content experts, observation sheets to evaluate the animated media, and a practicality questionnaire. Data analysis for validity and practicality was conducted using a Likert scale ranging from 1 to 5, while effectiveness data were obtained from pretest and posttest results and analyzed using the N-gain formula. The results of the media expert validation showed a percentage of 91.67%, categorized as “highly valid.” Meanwhile, the content expert validation reached 100%, also categorized as “highly valid.” The teacher response questionnaire yielded a percentage of 96.67%, categorized as “highly valid,” while the student response questionnaire yielded a percentage of 91.12%, also categorized as “highly valid.” Additionally, the N-gain calculation yielded an average score of 0.62, which falls into the “moderate” category. This indicates significant progress in student learning outcomes